Combined hormonal contraceptives and the risk of venous and arterial thromboembolism and cardiovascular death: misuse of automated databases. Issue 2 (14th March 2013) - Shapiro, Samuel
Abstract : Background: In December 2011, the US Food and Drug Administration (FDA) convened a public Advisory Committee meeting to review evidence from a study commissioned by the agency. An analysis of findings derived from four databases was published on the FDA website, and presented at the meeting. Among users of combined hormonal contraceptives containing ethinylestradiol (EE) plus drospirenone (DRSP) the risks of venous (VTE) and arterial thromboembolism (ATE) were higher than among users of older reference contraceptives containing other progestogens. The findings have now been published in a peer-reviewed journal. Objective: To evaluate the published evidence. Methods: Generally accepted epidemiological principles of causality are applied. Results: The findings did not satisfy the criteria of time order, bias, confounding, statistical stability and strength of association, duration-response, internal consistency, external consistency, or biological plausibility. Conclusions: The best evidence continues to suggest that the increased risk of VTE in combined hormonal contraceptive users is dependent on the dose of estrogen, and independent of the progestogen used. The best evidence also suggests that DRSP does not increase the risk of ATE, and may reduce it.